The role of nutrition in achieving more sustainable and environmentally friendly aquaculture: Review - Csaba, Hancz (Acta Agraria Kaposváriensis, 2024)
Sustainability applies to almost all aspects of human activity, and the ever-growing aquaculture industry is no exception. Feeding aquatic animals is of paramount importance in terms of economic and environmental sustainability. This review discusses practices and promising new results for improving feed efficiency at different levels of production intensity. Special emphasis is placed on demonstrating how semi-intensive pond technology can be considered ab ovo sustainable also from a social point of view. Recent achievements in the field of alternative protein sources to replace fishmeal are also discussed, as well as the beneficial properties of special feed additives such as probiotics and phytochemicals.
Keywords: akvakultúra; takarmányozástan; fenntarthatóság